THE IMPACT OF MORPHOLOGICAL AND BASIC MOTOR DIMENSIONS ON PERFORMING THE SITUATIONAL-MOTOR DUTY IN HANDBALL - Mimoza Xhemaili (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The research has been made in order to certify the level of anthropometric and motor features impact as predictive (independent) variables on completion of situational-motor test as criteria (dependent) variable. This research has included the sample of 60 young handball players aged 17 and 18 of Handball Club Drita from Gjilan. The variables sample was composed of a group of ten tests; four anthropometric variables and five motor tests as predictive variables and one situational-motor test as a criteria variable. For each anthropometric, motor and situational-motor variable central dispersive and statistical parameters have been considered. In order to evaluate their predicative results and criteria connection the regressive analysis has been applied. Correlation results of criteria variable and anthropometric and motor (predictive) system variable; it shows that there is an important statustucak connection between criteria variable (throwing of the ball with interruption from a 6 meters distance group into the square 1x1 m in one minute) and the predictive system. Out of four anthropometrical variables and five motor tests, only the motor variable - long leap from the spot - MLLFS. (Beta) = 0.517 is important to P = 0.000 level.